KAKO SE MOGU PODUČAVATI STRATEGIJE PAMĆENJA TEKSTA - Danica Pirsl; Nenad Zivanovic; Petar Pavlović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Cognitive strategies help out learners in general to make learning process more efficient and to activate previous knowledge which in turn helps out remembering and retrieval of infomation. Therefore following techniques are used widely: advance organizers, analogy, elaboration, inference, questions of different types. Thus we help out our students to better organize their learning styles and learn from texts.